Phosphorylated lipid-conjugated oligonucleotide selectively anchors on cell membranes with high alkaline phosphatase expression - Cheng Jin (Nature Portfolio, 2019)
Membrane-anchored DNA probes have been used to study molecular interactions and control cell assembly, but are not selective for different cell membranes. Here the authors develop a lipid-conjugated oligonucleotide for alkaline phosphatase-dependent cell membrane anchorage and use it to distinguish different cancer cells.